An exploration of the factors associated with paediatric burn injuries in rural and peri-urban Malawi - Beard, Maria (2018)
Background: Burn injuries disproportionally affect the world’s poorest regions. However, there is a lack of data from these areas to determine the true extent of this public health problem. Children in Malawi are at high risk of burn injuries and poor health because of the nature of their environment, and the paucity of burn prevention programmes. At present, the research that reflects the factors associated with these injuries has been limited to the interpretation of quantitative, hospital based data, which may provide patterns of burns risks, but does not reflect the context or perception of burn injuries necessary to create culturally appropriate and targeted prevention initiatives. Moreover, while it has been suggested that the use of improved cookstoves (ICS) in these areas might mitigate children’s exposure to burn injuries more research is needed.